Transformasi Rumah Panggung Masyarakat Loloan Timur dalam Pemajuan Kebudayaan - Wiasti, Ni Made; Arjani, Ni Luh (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p08, 2021)
Traditional technology is one of cultural advancement objects that can be found in Loloan stilt houses which are undergoing transformation and decline in quantity. This paper aims to know shape and determinants of stilt houses transformation in East Loloan, as well as to reveal the implications in terms of cultural advancement program. The study applied qualitative methods which were analyzed interpretive descriptive. The results showed that the stilt house consist two forms and has three levels based on the cosmological community. Transformation of houses on stilts, namely addition of space and changes in function of underside caused by determinants: social change, cultural dynamic, transition livelihoods, technology development, activity change, family members structure, build condition, land area, and interest of homeowner. The implication is that most of the aspects of the cultural advancement program have been fulfilled, except for the coaching aspect which has not been touched by community or government.